Orthopaedics for the physical therapist assistant - Dutton, Mark (Jones & Bartlett Learning, 2012)
Orthopaedics for the Physical Therapist Assistant provides the physical therapist assistant (PTA) student with a broad overview of orthopaedics as it relates to physical therapy. This is the first book to combine kinesiology, orthopedic management, and therapeutic exercise; tying in the anatomy and kinesiology to the examination and pathology of each of the joints. This comprehensive text describes the anatomy and biomechanics of each area of the spine, pelvis, and TMJ. Working from this foundation, detailed explanations on the re-evaluation and treatment of each of the various areas are given with an emphasis on techniques that are evidence-based. This text also includes chapters on pediatrics, geriatrics, manual therapy, and women s health. Each chapter includes learning objectives, key terms, key point boxes, a summary, suggested readings, references, and end-of-chapter review questions to test the students understanding of the material.